2013
DOI: 10.3390/en6020871
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects of Sewage Sludge Carbonization and Other Treatment Alternatives

Abstract: Carbonization is a newly developed process that converts sewage sludge to biocoal, a type of solid biomass that can partially substitute for coal during power generation. This study presents an assessment of the environmental effects of various sewage sludge treatment processes, including carbonization, direct landfills, co-incineration with municipal solid waste, and mono-incineration in Taiwan. This assessment was conducted using the life cycle assessment software SimaPro 7.2 and the IMPACT2002+ model. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The use of biological fertilizer in place of synthetic fertilizer improves the energy performance of the system while negatively affecting each of the environmental impacts. Although outside the scope of this study, alternative methods of disposal of sewage sludge such as by landfill or incineration may results in higher emissions than land application (Wang et al 2013).…”
Section: Alternative Fertilizersmentioning
confidence: 96%
“…The use of biological fertilizer in place of synthetic fertilizer improves the energy performance of the system while negatively affecting each of the environmental impacts. Although outside the scope of this study, alternative methods of disposal of sewage sludge such as by landfill or incineration may results in higher emissions than land application (Wang et al 2013).…”
Section: Alternative Fertilizersmentioning
confidence: 96%
“…The performed research indicated that the form of biochar restrained the leaching of heavy metals [32], despite the concentrations being considerable when compared with the restrictions set by the regulations [33]. Wang et al performed an assessment of the environmental effects of the carbonization of sewage sludge and concluded that it may have an overall positive environmental impact in comparison with landfilling and incineration [34].…”
Section: Torrefaction Of Sewage Sludgementioning
confidence: 99%
“…Indeed, the so-called city-gas was stored in gazometers which can be found in most of the big cities around Europe and recognized as industrial heritage. Nowadays, minimization of waste production is essential for a more sustainable development of society, but energy harvesting from its flow is the most feasible option to handle the society transition [3] along with the implementation of promising renewable technologies [4,5]. Based on technical and legal regulations waste is classified for treatment or harnessing for energy purposes according to its physical and chemical composition.…”
Section: Introductionmentioning
confidence: 99%